Crystalglobulinemia in Multiple Myeloma: A Rare Case Report of Survival and Renal Recovery. (May 2020) - Chou, Angela; Long, Christopher; Vonthethoff, Leon; Ho, Shir-Jing; Pettit, Franziska; Badve, Sunil V.
Rationale: Crystalglobulinemia is a rare complication of monoclonal gammopathy wherein crystallized immunoglobulins deposit in various organs causing occlusive vasculopathy, endothelial damage, and thrombosis. It should be differentiated from light chain cast nephropathy without crystalline nephropathy through timely diagnosis with a kidney biopsy. Presenting concerns of the patient: We report a case of a 74-year-old female with polyarthralgia, chest pain, petechial rash, and acute kidney injury. Diagnoses: Kidney biopsy revealed eosinophilic casts in the tubular lumen and similar occlusive crystalline deposits within the glomerular vasculature and interlobular arteries. Bone marrow biopsy and serum electrophoresis confirmed immunoglobulin G (IgG) κ multiple myeloma. Interventions: Dialysis was initiated for severe oligoanuric acute kidney injury. The patient was treated with 5 sessions of plasmapheresis and 11 cycles of clone reduction chemotherapy with CyBorD (cyclophosphamide, bortezomib, and dexamethasone). Outcomes: This patient achieved excellent kidney recovery and is no longer dialysis dependent. Teaching points: Crystalglobulinemia should be suspected in patients with rapidly progressive acute kidney injury and monoclonal gammopathy. Timely investigation with kidney biopsy to differentiate this condition from light chain cast nephropathy and initiation of appropriate treatment can lead to remission of disease and excellent recovery of kidney function.